1991
DOI: 10.1111/j.1475-682x.1991.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and Accuracy of Recall in the Diffusion of the News From a Newspaper vs. a Television Source

Abstract: The study of the word‐of‐mouth flow of news to audiences is an important if somewhat neglected topic. First, this may be the only means by which some citizens receive information about events and issues in their community. Second, in disaster situations many people cannot be reached by conventional means, and critical information comes to them by word‐of‐mouth. The present experiment makes use of the Allport and Postman design for the study of the changes (leveling and sharpening) that messages undergo as they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For instance, consumers may have known about the intervention message, or been affected by it, but may not have realised what we were referring to during the survey. Additionally, the finding that respondents with inaccurate message recall mostly cited family and friends as the message source, rather than social media and news, speaks to the diminished accuracy of word-of-mouth information [ 43 ]. Lastly, when recounting behaviour, it is expected that some individuals will inaccurately recall their own behaviour, or possibly downplay behaviour they think is socially undesirable [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumers may have known about the intervention message, or been affected by it, but may not have realised what we were referring to during the survey. Additionally, the finding that respondents with inaccurate message recall mostly cited family and friends as the message source, rather than social media and news, speaks to the diminished accuracy of word-of-mouth information [ 43 ]. Lastly, when recounting behaviour, it is expected that some individuals will inaccurately recall their own behaviour, or possibly downplay behaviour they think is socially undesirable [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[22] DeFleur et al compared the dissemination effect between newspaper and television, and they believed that newspaper will give readers a deeper impression. [23] Steven Chaffee et al found that the channels from which Americans get political information are changing from television and newspapers to news, magazines and radio. [24] In all, these studies were detailed, but most of them only focused on a single medium.…”
Section: Introductionmentioning
confidence: 99%